Tip-Oriented Closed Rhinoplasty Built on Septocolumellar Suture and a New Caudal Septal Graft Technique - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Background: A beautiful and appealing nose receives the greatest contribution from the nasal tip subunit, which should be regarded as the primary center of attention during a rhinoplasty procedure. In achieving the desired shape and position of the nasal tip during closed rhinoplasty, the septocolumellar suture functions as the major determinant together with the caudal portion of the septal cartilage, which has a significant influence on the versatility of the septocolumellar suture. The purpose of this study was to present the analysis of the indications, the technical steps, and the advantages of caudal septal graft and septocolumellar suture utilization in closed rhinoplasty. Methods: The septocolumellar suture with or without the caudal septal graft combination procedure has been performed in 2286 patients via a closed rhinoplasty approach. Intraoperatively, the septal cartilage at hand was thoroughly evaluated and one of the 5 types of caudal septal grafts was used when necessary. After the establishment of a strong and straight septal cartilage with sufficient height and length, 4 different septocolumellar sutures in a specific order were used to modify the relationship between the lower lateral cartilages and the nasal septum. Results: Of the 2286 cases, 1837 (80.3%) were primary and 449 (19.7%) secondary rhinoplasties, which have been followed up for 9 to 48 months. The caudal septal graft was combined to the septocolumellar suture in 621 (27.1%) patients. Of the caudal septal grafts, 69.7% were used for primary rhinoplasty cases, and 30.3% for secondary rhinoplasties. At the 18th month postoperatively, tip projection was found to be satisfactory for 98% of the patients. Conclusions: The septocolumellar suture combined with caudal septal graft in closed rhinoplasty substantially facilitates the achievement of a cosmetically and functionally pleasing end result, bringing the solution for a wide array of problems such as short nose, supratip deformity, nasolabial angle change, or columellar bowing. Nevertheless, the technique has a steep learning curve; therefore, a meticulous preoperative evaluation should be exerted, a precise surgical planning should be prosecuted, and an excessive reduction of the nasal tip or exaggerated columellar retraction should be avoided.
Keywords: closed rhinoplasty; septocolumellar suture; nasal tip; septal graft; NASAL TIP; EXTENSION GRAFT; SHORT-NOSE; CARTILAGE; SURGERY